Two ’moments in time’ during Middle Stone Age occupations of Sibudu, South Africa - Wadley, L. (Southern African Humanities, 2012)
Sibudu, KwaZulu-Natal, South Africa, has good organic preservation that results in the occasional discovery of ’moments in time’. Two such moments are described here. One is at 77.2 ± 2.1 thousand years ago (ka) when deliberately constructed bedding probably served as a work area as well as a sleeping place. Sedge leaves and stems were laid directly on the shelter floor and then covered with Cryptocarya woodii leaves. These River Wild Quince leaves are insect-repelling and their use provides early evidence for the exploitation of medicinal plants. The second ’moment in time’ described here is at 70.5 ± 2.0 ka, in a Still Bay Industry. Perforated Afrolittorina africana marine shells, one of which has red ochre stains, were found clustered with some unperforated shells close to small combustion features. The assemblage may represent an area where beads were made or where apparel was decorated. Rock fall from the roof of the shelter influenced the placement of features and the organization of activities. A large rock fall event occurred after the use of the insect-repelling bedding at 77 ka, but before 73 ka. The rocks affected all later occupations until the more recent Howiesons Poort ones at 64 ka.